A novel high-efficient imidazoline derivative corrosion inhibitor for carbon steel in CO2-containing oilfield produced water: experimental and theoretical studies - Ganghua Huang; Wen Chen; Chao Miao; Cong Shen; Yong bo Wang; G. A. Zhang (BMC Chemistry)
Abstract During the oil and gas extraction, the corrosion of carbon steel pipelines poses a serious threat to the safe production of oil and gas. The use of corrosion inhibitors is one of the effective methods to solve this tough issue. In this work, a novel dimmer acid imidazoline derivative (DIMTU) was developed as corrosion inhibitor for carbon steel in CO2-containing oilfield produced water. The experimental test results show that DIMTU has outstanding corrosion inhibition effects, with an inhibition efficiency of 98.54% at the concentration of 250 ppm. Quantum chemical calculations indicate that the introduction of thiourea into dimmer acid imidazoline can significantly increase the adsorption sites, effectively improving the adsorption ability of DIMTU. GTN-xTB calculations reveal that DIMTU molecule could strongly adsorb on the steel surface through the bonding of the S, N, C atoms of imidazoline ring and thiourea fragment to steel surface. The adsorbed DIMTU film could prevent the contact of corrosion species to the steel surface and effectively suppress the corrosion of steel.